Harnessing open access databases to improve scholarship: perception of professionals at the frontline - Emezie, Nkeiru Amauche; Ezeri, Chioma Nnalu; Ewulo, Ruth Olasumbo (International Journal of Knowledge Content Development & Technology, 2023)
The study investigated perception of librarians on their roles in using open access databases to improve scholarship. Descriptive survey design was used for the study while questionnaire was employed to collect data from 53 professional librarians at two federal universities in the eastern and western part of Nigeria. Findings from the survey reveal that librarians need to collaborate with faculties to develop institutional repositories and, raise awareness of open access databases in the university community among others. Various factors that could hinder librarians from effectively discharging these roles were identified. Some of which include administrative bottlenecks, poor internet facilities and lack of navigational skills. The study recommends acquisition of necessary knowledge and skills to enable librarians add value to their services and remain at the frontline of information provision.